Reference values for spirometry and their use in test interpretation: A Position Statement from the Australian and New Zealand Society of Respiratory Science - Brazzale, D.; Hall, Graham; Swanney, M. (Wiley-Blackwell Publishing Asia, 2016)
Traditionally, spirometry testing tended to be confined to the realm of hospital-based laboratories but is now performed in a variety of health care settings. Regardless of the setting in which the test is conducted, the fundamental basis of spirometry is that the test is both performed and interpreted according to the international standards. The purpose of this Australian and New Zealand Society of Respiratory Science (ANZSRS) statement is to provide the background and recommendations for the interpretation of spirometry results in clinical practice. This includes the benchmarking of an individual's results to population reference data, as well as providing the platform for a statistically and conceptually based approach to the interpretation of spirometry results. Given the many limitations of older reference equations, it is imperative that the most up-to-date and relevant reference equations are used for test interpretation. Given this, the ANZSRS recommends the adoption of the Global Lung Function Initiative (GLI) 2012 spirometry reference values throughout Australia and New Zealand. The ANZSRS also recommends that interpretation of spirometry results is based on the lower limit of normal from the reference values and the use of Z-scores where available.